Pengaruh Kepribadian, Keluarga, Human Capital terhadap Karir dan Kinerja Manajer (Studi pada Perbankan di Makassar) - Idayanti, Idayanti (Jurnal Aplikasi Manajemen, 2009)
This research was conducted based on the fact that individual behavior plays an important role to determining the career success of male and female managers. The Career success departs from the personality because the individual remains under the effect of personality. In addition, family responsibility also affects the individual opportunity to progress. The working individuals need special skill and knowledge other than family and personality, as expected by human capital theory. Respondent involves 102 managers. Results of research indicate that first, the personality, family and human capital have significant positive effect on objective career but not for subjective career; second, objective career brings the significant positive effect on subjective career; third, personality, family and human capital have indirect effect on subjective career through objective career; and have significant positive on performance managers.